cdh23 affects congenital hearing loss through regulating purine metabolism - Yang, Shu; Xie, Bing-Lin; Dong, Xiao-ping; Wang, Ling-xiang; Zhu, Gang-hua; Wang, Tian; Wu, Wei-jing; Lai, Ruo-sha; Tao, Rong; Guan, Min-xin; Chen, Fang-yi; Tan, Dong-hui; et al. (Frontiers in Molecular Neuroscience, 2023)
Introduction The pathogenic gene CDH23 plays a pivotal role in tip links, which is indispensable for mechanoelectrical transduction in the hair cells. However, the underlying molecular mechanism and signal regulatory networks that influence deafness is still largely unknown. Methods In this study, a congenital deafness family, whole exome sequencing revealed a new mutation in the pathogenic gene CDH23, subsequently; the mutation has been validated using Sanger sequencing method. Then CRISPR/Cas9 technology was employed to knockout zebrafish cdh23 gene. Startle response experiment was used to compare with wide-type, the response to sound stimulation between wide-type and cdh23−/−. To further illustrate the molecular mechanisms underlying congenital deafness, comparative transcriptomic profiling and multiple bioinformatics analyses were performed. Results The YO-PRO-1 assay result showed that in cdh23 deficient embryos, the YO-PRO-1 signal in inner ear and lateral line neuromast hair cells were completely lost. Startle response experiment showed that compared with wide-type, the response to sound stimulation decreased significantly in cdh23 mutant larvae. Comparative transcriptomic showed that the candidate genes such as atp1b2b and myof could affect hearing by regulating ATP production and purine metabolism in a synergetic way with cdh23. RT-qPCR results further confirmed the transcriptomics results. Further compensatory experiment showed that ATP treated cdh23−/− embryos can partially recover the mutant phenotype. Conclusion In conclusion, our study may shed light on deciphering the principal mechanism and provide a potential therapeutic method for congenital hearing loss under the condition of CDH23 mutation.